‘Of war and war’s alarms’: W.B. Yeats from On the Boiler (1939) - Adrian PATERSON (E-REA)
On the Boiler is W.B. Yeats’s last piece of completed prose. Published posthumously through his family’s Cuala Press in 1939, it represents what appears to be his final authorized word on politics, on education, on aesthetics, on war and peace. Controversial, and in places unpalatable, of all Yeats’s published prose it is that which comes closest to fascism. It is also a serious meditation on art and European politics by a major poet. In any analysis of modernist nonfictional prose concerning war, On the Boiler should not be ignored. This essay argues that On the Boiler, hybrid and contradictory as it is, does not represent an anomaly, but a continuation. Yet it is also contingent, occasional, and conditional, and must therefore be examined as a printed object formally, paratextually, and contextually in order to understand the full resonance of its incendiary charge.